Mengembangkan Penjualan Produk Bawang Merah di Lingkungan Desa Ngadiboyo Kecamatan Rejoso Kabupaten Nganjuk - Hendra Maulana; Ajeng Arum Isfania; Yolanda Irfania; Muhammad Rizki Firmansyah; Ignatius Bramantya Prasetyo Dewa; Hannah Emmanuella Delia (Universitas Katolik Widya Karya Malang, 2023)
Nganjuk is a Kabupaten in the province of East Java, Indonesia. One of the sub-districts in Nganjuk, Rejoso sub-district, Ngadiboyo village, is a potential producer of shallots. We found that the Ngadiboyo village area is a potential producer of shallots. In addition to shallots, residents use their farmland to grow commodities such as soya and green beans. However, the problem we identified with the village's economy is the need for home industry-based businesses that utilize the main crops to be sold as ready-to-consume products. On this occasion, we want to develop the sale of shallot products to increase the economic stability of the Ngadiboyo Village community. Community service is carried out with a mentoring method through attracting community participation. Assistance to attract participation is focused on developing sales through social media, product photos, and e-commerce. Sales development activities on shallot products are one of the activities to help increase community sales. Implementing this activity is expected to increase sales to help the economy. Therefore, this community service activity is hoped to change the community of shallot product sellers.